Letter from Durand Churchill, Jr. to Arnold O. Beckman - Churchill, Durand, Jr. (1945)
Letter regarding the extension of the military contract for Beckman Instruments' Pauling Oxygen Meter development. This letter also mentions the possibility of using the instrument inside oxygen tents. Developed from a Linus Pauling design during WWII, the technology behind Beckman Instruments’ oxygen analyzers ended up doing such diverse jobs as monitoring astronauts’ respiration, maintaining packaged food safety, and preventing blindness in newborn babies.
Keywords: Scientific apparatus and instruments; Oxygen--Measurement; World War (1939-1945); United States. Office of Scientific Research and Development. National Defense Research Committee; Beckman Instruments, Inc.